Pedagogical Competence of Arabic Language Teachers Based on the National Education Standards - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (Gunung Djati Conference Series, 2025)
This study aims to examine the pedagogical competence of Arabic language teachers in accordance with the National Education Standards. A descriptive qualitative approach was employed to provide an in-depth depiction of teachers’ pedagogical competence based on these standards, covering the stages of lesson planning, implementation, and evaluation. Primary data were obtained through interviews, observations, and documentation, while secondary data were collected from official documents and relevant literature. Data collection techniques included observation, semi-structured interviews, and document analysis with triangulation to ensure accuracy. Data analysis followed the Miles and Huberman model through reduction, presentation, and inductive conclusion drawing to produce valid and contextual findings. The results indicate that the pedagogical competence of Arabic language teachers encompasses understanding students, planning, implementing, evaluating, and developing learners’ potential by integrating language skills and Islamic values. Teachers are required to master learning theories, develop curricula, utilize technology, and conduct valid assessments. Moreover, teachers are expected to foster students’ creativity and 21st-century skills, thereby making learning more effective, meaningful, and aligned with the National Education Standards. This study recommends enhancing the pedagogical competence of Arabic language teachers through continuous professional development, integration of educational technology, and strengthening of Islamic value-based curricula to support students’ 21st-century skills.